PENGUATAN WILAYAH BINAAN MANDIRI ENERGI MELALUI PENINGKATAN KAPASITAS MIKROHIDRO DI DAERAH TERPENCIL - Asmaranto, Runi; Sugiarto, Sugiarto; Widhiyanuriyawan, Denny; Purnomo, Mangku (Jurusan Teknik Pengairan, Fakultas Teknik, Universitas Brawijaya, 2020)
Tanah Merah is an isolated hamlet in the village of Batur that has not been reached by PLN electricity because its geographical is on the slopes of Mount Argopuro and far from the village center. To achieve this just by walking or riding a motorcycle as far as 3 km. In Tanah Merah, micro hydro has been developed from the Kedung Sumur River discharge, but it is not yet optimal. A collaboration was held by BPPM FT UB with CSR of PT PGN (Persero) in 2016, but has not been able to resolve the limited power generated for 500 families. Another potential community is farmers and breeders. Most livestock activities carried out by the community are 267 head of beef cattle with the distribution of cattle farmers in RT 8 totaling 107 households, RT 9 totaling 95 households and RT 10 totaling 62 households averaging 2 cows. With such a large number of cattle, it is of course also produced a large amount of livestock waste. Based on these problems, the UB Community Service Team through the Serving Doctoral Program wants to help partner communities solve existing problems in order to improve their welfare. Efforts are being made to empower community groups of micro-hydro (PLTMH) through the use of renewable energy, namely increasing micro-hydro electricity capacity and empowering micro-hydro-based economies.